Halolysin SptA, a Serine Protease, Contributes to Growth-Phase Transition of Haloarchaeon Natrinema sp. J7-2, and Its Expression Involves Cooperative Action of Multiple Cis-Regulatory Elements - Li, Moran; Yin, Jing; Mei, Sha; Wang, Xuhong; Tang, Xiao-Feng; Tang, Bing (Frontiers in Microbiology, 2018)
Many haloarchaea produce extracellular subtilisin-like proteases (halolysins) during late log phase; however, the physiological function and regulatory mechanism of growth phase-dependent production of halolysins are unknown. Halolysin SptA, the major extracellular protease of Natrinema sp. J7-2, is capable of intracellular self-activation to affect haloarchaeal growth. Here, we report that deletion of sptA leads to loss of extracellular and intracellular protease activities against azocasein and/or suc-AAPF-pNA, as well as a change in growth-phase transition of the haloarchaeon. Our results suggest that SptA is important for strain J7-2 to enter the stationary and death phases. Deletion and mutational analyses of the 5’-flanking region of sptA revealed two partially overlapping, semi-palindromic sequences upstream of the TATA box act as positive and negative cis-regulatory elements, respectively, to mediate sptA expression in late log phase. Additionally, a negative cis-regulatory element covering WW motif and a distant enhancer contribute to the modulation of sptA expression. Our results demonstrate that SptA functions both extracellularly and intracellularly, and that sptA expression relies on the cooperative action of multiple cis-regulatory elements, allowing SptA to exert its function properly at different growth stages in strain J7-2.